The incidence of post-operative sore throat in Bloemfontein Academic Hospital in May-September 2016 - Vuthela, S. P. (University of the Free State, 2017)
Background: Endotracheal intubation is frequently used during general anaesthesia to secure patients airway, prevent aspiration and to provide for positive pressure ventilation. Post operative sore throat is one of the many complications of endotracheal intubation. Objectives: The aim of the study is to determine the incidence of post operative sore throat in Bloemfontein Academic Hospital Complex in healthy ASA 1 & 2 patient undergoing general anaesthesia. Methods: In this Prospective descriptive observational study, 201 patients, aged 18-60 years, undergoing general anaesthesia (with ETT or LMA), for elective surgery in the Bloemfontein Academic Hospital Complex during May 2016 till September 2016 were included in the study. Before induction of anaesthesia, the attending anaesthetist registrar or consultant obtained consent from the participants for the study. After the operation, the primary outcomes (Post-op sore throat) was assessed in the recovery room before discharge to the ward, in the ward at 2 and 6 hours postop. Post operative sore throat was assessed on a 1-10 Verbal Numerical Pain scale where 1-3=no sore throat, 4-7= significant sore throat and 8-10= Severe sore throat. Results: A total of 235 patient s were enrolled in the study. 34 patients were excluded from the study,16 were older than 60 years of age, 13 had emergency procedures and 5 incomplete data sheets. Data for 201 patients was analysed, in the recovery room: 51.24% of patients had no sore throat, 37.32% had significant sore throat and 11.4% had severe sore throat. At 2 hours: Post-Op, 78.6% had no sore throat, 19.4% had significant sore throat and 1.9% had severe sore throat. At 6 hours: 94% had no sore throat, 4% had significant sore throat and 2% had severe sore throat. Proportion of patients with hoarseness was 7.46%, 3,98% and 4.96% in the recovery room, at 2 and 6 hours respectively. The incidence of cough was 21,89%, 9,45% and 3% in the recovery room, at 2 and 6 hours post-op respectively. Conclusion: Using a ten point numerical pain rating score, the incidence of post operative sore throat in our study was found to be 48.8% in the recovery room, 21.4% and 6% at 2 and 6 hours post-op respectively. Our study recommends that further studies should be done to determine if this sore throat leads to any morbidity or patients dissatisfaction and to explore measures that can be used to minimise sore throat post operatively.
Keywords: Sore throat; Endotracheal intubation; Anaesthesia; Patient’s trachea; Dissertation (M.Sc. (Anaesthesiology))--University of the Free State, 2017